Efektifitas Penggunaan Fitur Instagram Dalam Meningkatkan Pertemanan Remaja SMA Negeri 1 Maros Di Era Digital - Muhammad Iqbal Sultan (Avant Garde, 2020)
The development of new media technology presents social media, especially Instagram, to share information and fulfill the needs of friendship among millennial teenagers. The trend of Instagram increased after Facebook was chosen by millennial teenagers to increase friendships in cyberspace, through photo uploads, Story Archives, Live Videos, Explore, and Highlights. This study analyzes the effectiveness of Instagram's features in increasing teenage friendship in the digital era. The research method used quantitative descriptive through a survey category among millennial adolescents. The technique of withdrawing informants using non-probability sampling uses proportional sampling. Determination of the sample using Isaac and Michael, the error rate of 5% was chosen by 67 respondents. Data collection techniques through questionnaires and literature study that are relevant to the research. The results showed that the effectiveness of Instagram's features in increasing teenage friendship in the digital era was dominant in the Close Friends feature as much as 61.2%. The comparison with other Instagram features, such as Story Archive, Explore, Live Video, and Highlights is minimal, increasing the effectiveness of friendships among teenagers. The Close Friends feature was chosen for reasons of self-disclosure and the convenience of uploading Instagram Stories. The level of openness in the category is high because of the proximity factor to choose and share uploads on this feature. The Close Friends feature is more privacy for Instagram users because of the freedom to choose friends and upload uploads based on their wishes.